ANALISIS KEWENANGAN HAKIM KONSTITUSI DALAM MENAFSIRKAN PERATURAN PERUNDANG-UNDANGAN BERDASARKAN UNDANG-UNDANG NOMOR 48 TAHUN 2008 TENTANG KEKUASAAN KEHAKIMAN - Rizda Ardyati; Evitha A Carollina (Universitas Slamet Riyadi, 2019)
This research is motivated by the decision of the Constitutional Court often to make legal breakthroughs accompanied by a logic of law that is less precise and anti accountability. This study is a normative legal research that is perspective with a legal approach and a conceptual approach. The legal material collection technique used in this study is literature study. The legal material analysis technique used by researchers in this study is the deduction method. The results of research and discussion produce conclusions, namely; First, the juridical basis of the authority of constitutional justices in interpreting statutory regulations can be seen from Article 5 paragraph (1) and Article 10 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power which means that any case faced with the court is not may refuse to examine, hear and decide on the case. Obviously or not the law governing the case, constitutional judges still have to explore the legal values and sense of justice that lives in society. Second, the principles of the administration of judicial power have been applied every time a Judicial Review is conducted. This can be seen in every decision where the decision always reflects the sense and values of justice that live in the community.